واقع مساهمة المرأة في النشاط الاقتصادي في محافظة اللاذقية - عكروش محمد; زمزم ميس (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يعد تمكين المرأة من أهم القضايا المتعلقة بمساهمة المرأة في النشاط الاقتصادي في محافظة اللاذقية ,وبالتالي فإن مقدار مشاركتها في النشاط الاقتصادي يمكن اعتباره من أهم مقاييس التنمية الاقتصادية . وبناء على ذلك تم في هذا البحث استعراض أهم المؤشرات الديمغرافية وأبرز الخصائص الاقتصادية المتعلقة بالمرأة , إضافة إلى مساهمة المرأة في القطاعات الاقتصادية حسب الحالة العملية وحسب المهنة. كما تم التطرق إلى أهم الأسباب التي تعيق تقدم المرأة في سوق العمل ومن اهم النتائج التي تم التوصل إليها: - يوجد أثر ذو دلالة إحصائية لعمر المرأة على مساهمتها في النشاط الاقتصادي. - يوجد أثر ذو دلالة إحصائية للمستوى التعليمي للمرأة على مساهمتها في النشاط الاقتصادي. - يعتبر العمل الإضافي المزدوج من أهم الصعوبات التي تعانيها المرأة في عملها . - يوجد أثر ذو دلالة إحصائية لمهنة المرأة على مساهمتها في النشاط الاقتصادي. وعلى ضوء النتائج السابقة تم اقتراح مجموعة من التوصيات التي تساعد على مواجهة المعوقات التي تقف في طريق مساهمة المرأة و تفعيل مشاركتها في جميع أوجه النشاط الاقتصادي. The subject of women and empowering is the most important issues related to the contribution of women in the economic activity in the province of Lattakia , Thus, the amount of participation in economic activity can be regarded as the most important measure of economic development. This research reviewed the most important the most important demographic indicators highlighted the economic characteristics of the women , in addition to the contribution of women in the economic sectors by employment status and by profession . In addition to the most important reasons that prevent the advancement of women in the labor market and the most important results that have been reached : - There is a statistically significant effect of age on the women’s contribution to economic activity. - There is a statistically significant effect of the educational level of women’s contribution to economic activity. - The Overtime double of the main difficulties faced by women in their work. - There is a statistically significant effect for career women on their contribution to economic activity In light of the previous results we got a set of recommendations that will enable us to face the obstacles that stand in the way of the contribution of women and activating their participation in all aspects of economic activity